Subharmonic Almost Periodic Functions of Slow Growth - Favorov, S.Yu.; Rakhnin, A.V. (Журнал математической физики, анализа, геометрии, 2007)
We obtain a complete description of the Riesz measures of almost periodic subharmonic functions with at most of linear growth on C. As a consequence we get a complete description of zero sets for the class of entire functions of exponential type with almost periodic modula.